O uso das TIC por professores da rede pública: as contribuições de uma formação continuada - Santos, Vanessa Lara (2018)
This work aimed to identify in the graduates of a specialization in technologies carried out by the UAB what were the contributions of a continuing training course for the pedagogical practice of the participants, presenting a reflection about the challenges faced by the graduates of a continuous training in ICT to apply which had been addressed in said course and understood if the principles proposed by the course were adopted. Therefore, a questionnaire was applied with space for the research participants to discuss each subject. A bibliographical research of the theme was also carried out to better contextualize the theme. Considering the objectives of this study, a qualitative approach was used to consolidate the answers obtained in a more descriptive way, reflecting on what happened in the training process, using the questionnaire and the interview as a method of collecting data, systematizing the respondents' speeches on the course contributions, challenges and principles provided by the course. With the research, it was noticed that this training provided significant changes in the pedagogical achievement of the interviewees, in their relationships within the school space, but there is still a lot to be done, such as the monitoring of those coming from this type of training, so that to understand the scope of continuing education